Analysis and Simulation of Collaborative Space of the Dual Arm 6R Service Robot - Li Xianhua; Sun Qing; Fan Kaijie; Zhang Leigang (Jixie chuandong, 2018)
Aiming at collaborative space problem of the dual arm 6 R service robot,the Monte Carlo and traversal search comparison method are used for analysis according to its configuration characteristics. Firstly,according to the configuration of the manipulator,the standard DH method is used to construct the model,and then the forward kinematics equation of the arms is obtained. Secondly,the work space of each arm is got by using Monte Carlo method. Then,the collaborative space of the arms is obtained by using the traversal search comparison method,and the range of the joint angle of the dual arms is obtained through kinematics inverse method. Finally,the MATLAB toolbox is used to build the simulation platform and the algorithm is written to verify the correctness of the above analysis,and the foundation for the follow-up coordinated operation and trajectory planning is laid.